(untitled) (European Journal of Education and Psychology, 2018)
The programs to promote self-regulated learning in higher education are increasing. At the same time, the implementation of these programs through computer based learning environments is also rising. This paper contrasts the satisfaction of a self-regulation strategies training program implemented in two different formats, in the classroom and in a virtual environment, in order to determine if there is any difference between them. The sample consisted of 370 students from a university in the north of Spain. The results suggest greater effectiveness of the program carried out in the virtual environment. Results are discussed based on the controversy between the motivating potential of these virtual environments versus the difficulties that they can add to the learning process itself.